Impact of hospital formulary intervention on carbapenem use: a segmented time-series analysis of consumption and a propensity score-matched non-inferiority study of treatment efficacy - Nakaba Okamura; Ayano Katagiri; Tomoya Komori; Kei Kawanabe; Hirofumi Koike; Yukiko Sahashi; Rie Kubota (Journal of Pharmaceutical Health Care and Sciences)
Abstract Background Pharmaceutical formularies play a crucial role in guiding medication use by balancing clinical effectiveness and cost efficiency. Although formulary implementation has been increasing in Japan, comprehensive evaluations of its impact on both clinical and economic outcomes are limited. This study aimed to assess the effect of introducing an antimicrobial formulary at Yokohama City University Hospital on antibiotic usage and treatment outcomes in intra-abdominal infections. Methods We conducted a segmented time-series analysis to evaluate changes in carbapenem usage, including doripenem, before and after formulary implementation in October 2018. Monthly antibiotic consumption was measured by antibiotic use density (AUD). The primary outcomes were changes in doripenem use and treatment efficacy for intra-abdominal infections. To assess treatment efficacy, we used non-inferiority analysis with propensity score matching based on age, sex, body mass index, cancer status, and baseline blood test results. The treatment outcomes were evaluated using predefined clinical indicators. Results Following the formulary intervention, doripenem use significantly decreased from 10.8 to 4.9%, meropenem use slightly increased, and imipenem/cilastatin usage remained stable. Overall, carbapenem use significantly decreased during the study period. Treatment effectiveness for intra-abdominal infections remained non-inferior, with a higher proportion of patients classified as having an “effective” response post-intervention (86.6% vs. 79.4% pre-intervention). The confidence interval confirmed the non-inferiority margin, indicating no clinically significant reduction in treatment effectiveness following the formulary introduction. Conclusions The introduction of an antibiotic formulary at Yokohama City University Hospital effectively reduced the use of doripenem without compromising the effectiveness of treatment of intra-abdominal infections. These findings suggest that formulary management can be a valuable strategy for optimizing antibiotic use while maintaining clinical outcomes and contributing to improved antimicrobial stewardship in healthcare settings. Further research is warranted to explore the broader implications of formulary implementation in Japanese healthcare practices.